Knowledge and Attitude Towards First Aid Management in School Teachers - Jennifer W. Anthony1 , Sharadha Ramesh2 , Mangesh Jabade13 , Merlin Suji1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
First aid comes in the picture because it gives us first and foremost action required to prevent any complication.Compared to all other age group the school going children in a country are exposed to various kinds ofhealth related incidents like, bleeding, Fracture, skin cuts, burn, Heatstroke, etc. which may contribute tohigher mortality rate if not treated or not handled initially with appropriate care. Most of these incidentsoccur when the child is in school, hence it is essential for all the primary school teaches to be trained tohandle emergencies in school to prevent further various kinds of life threatening complications. Presentstudy aims to assess the level of knowledge regarding First Aid Management among selected school teachersof Pune City; to assess the Attitude regarding First Aid Management among selected school teachers of PuneCity; to find out association between Knowledge score and selected demographic variables and to find outassociation between Attitude score and selected demographic variables.1Methodology: A Non-Experimental Descriptive Research Approach was conducted among various schoolsof Pune City. The selection of sample was based on easy geographical accessibility, cooperation, andavailability of samples. The sample size for study was 60, selected by using Non Probability ConvenienceSampling Technique from various school of Pune City who met the inclusion criteria.Result: The analysis asserts that 82.66% of the school teachers shows Good knowledge regarding First AidManagement and 13.33% of the school teachers shows average knowledge regarding First Management.About 6.66% of total school teachers were found to have positive attitude towards First aid Management,whereas 88.33% of school teachers shown neutral reaction towards First Aid Management and 5% of theteachers were found to have Negative attitude towards First Aid Management.Conclusion: Knowledge related to First Aid Management among school teachers is found to be good andAttitude towards the same is Neutral. However the study proposes that First Aid Management trainingshould be given to all the school teachers to make school a safer place for children and prevent all the lifethreatening complication.